2008
DOI: 10.1111/j.1439-0485.2008.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of talitrid amphipods to a gradient of recreational pressure caused by beach urbanization

Abstract: Demands for public outdoor recreation and urbanization are a potential source of environmental disturbances, particularly on sandy beaches. These habitats have therefore experienced rapid degradation worldwide. Talitrid amphipods, which are common inhabitants of sandy beaches, are probably good indicators of such disturbances. In this study, we evaluated the responses of the two amphipods Talitrus saltator and Atlantorchestoidea brasiliensis to human pressure on Spanish and a Brazilian beach, hypothesizing tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 28 publications
(51 reference statements)
1
41
0
2
Order By: Relevance
“…Moreover, on reflective beaches on the Chilean coast, Jaramillo et al (1996) observed no negative impact on the abundance of this species. According to Veloso et al (2008), the low level of beach occupation studied by Jaramillo et al (1996) may have generated misleading results. Additionally, the authors provided no data on the intensity of trampling or the characteristics of beach urbanization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, on reflective beaches on the Chilean coast, Jaramillo et al (1996) observed no negative impact on the abundance of this species. According to Veloso et al (2008), the low level of beach occupation studied by Jaramillo et al (1996) may have generated misleading results. Additionally, the authors provided no data on the intensity of trampling or the characteristics of beach urbanization.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, anthropogenic interference should be considered carefully, the different intensities and frequencies of impact beyond the recreational patterns, which vary from place to place, being taken into account (VELOSO et al, 2008). This study aimed to study and compare the effect of human recreational activities on the abundance and richness of macrofauna of dissipative and reflective sandy beaches.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some studies illustrated an overall remarkable negative impact on supralittoral species as a result of human beach use (e.g. Fanini et al, 2005;Veloso et al, 2006Veloso et al, , 2008Ugolini et al, 2008) and shoreline modifications such as the construction of seawalls or beach nourishment actions (e.g. Bessa et al, 2013;Dugan and Hubbard, 2006;Fanini et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Bessa et al, 2013;Fanini et al, 2009;Jones et al, 2008; and coastal armouring (Dugan and Hubbard, 2006;Dugan et al, 2008;Walker et al, 2008). Still, human recreational activities have been recognised to negatively affect beach fauna due to the intensive use of beaches (Schlacher and Thompson, 2012;Schlacher et al, 2011;Ugolini et al, 2008;Veloso et al, 2008) and to the impact of off-road vehicles (e.g. Schlacher et al, 2008a;Sheppard et al, 2009;Schlacher and Lucrezi, 2010;Walker and Schlacher, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Assim, esses anfípodas têm sido apontados como bons indicadores de impactos, chegando inclusive a desaparecer de áreas impactadas (Weslawski et al, 2000;Nardi et al, 2003;Ugolini et al, 2004;Fanini et al, 2005;Veloso et al, 2008;.…”
Section: Introductionunclassified